2020
DOI: 10.1101/2020.11.18.388959
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heme is crucial for medium-dependent metronidazole resistance in clinical isolates ofC. difficile

Abstract: Until recently, metronidazole was the first-line treatment for Clostridioides difficile infection and it is still commonly used. Though resistance has been reported due to the plasmid pCD-METRO, this does not explain all cases. Here, we investigate resistance to metronidazole in a collection of clinical isolates of C. difficile. We find that nearly all isolates demonstrate a heme-dependent increase in the minimal inhibitory concentration for metronidazole, which in some cases leads to isolates being qualified … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…The study has some limitations; first, it should be noted that a previous study reported on a heme-dependent increase in the metronidazole-MIC of C. difficile isolates for metronidazole, which in some cases led to interpretation of reduced susceptibility (MIC > 2 mg/L) ( Boekhoud et al, 2020 ). Therefore, it is necessary to validate the MIC values of all the isolates with metronidazole- reduced susceptibility.…”
Section: Discussionmentioning
confidence: 97%
“…The study has some limitations; first, it should be noted that a previous study reported on a heme-dependent increase in the metronidazole-MIC of C. difficile isolates for metronidazole, which in some cases led to interpretation of reduced susceptibility (MIC > 2 mg/L) ( Boekhoud et al, 2020 ). Therefore, it is necessary to validate the MIC values of all the isolates with metronidazole- reduced susceptibility.…”
Section: Discussionmentioning
confidence: 97%